Oppression on women during the trojan war in Pat Barker’s The Silence of The Girls - Nisrina Mumtaz; Linusia Marsih (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This study discusses the oppression on women due to social structure during the Trojan War in Pat Barker's The Silence of The Girls. There are two problem statements proposed in this study i.e. the social structure described and the forms of oppression on female characters reflected in The Silence of The Girls. This study is designed as descriptive qualitative study with sociological approach. The sociological approach is applied because this study deals with social structure in society and feminists’ point of view of oppression. The results of this study indicate that the social structure in Greek society are devided into several components, namely social structure based on class, gender roles, and culture. The social structure based on class indicates inequality between women and men. Women are inferior, while men are superior. The social structure of gender roles is based on the differences between men and women roles in society. Women are slaves and servants, while men are masters. The social structure based on culture is the social structure that has been formed in society, which positions women to obey men. The social structure creates differences between men and women. The position of women is under the men, so this leads to some oppression on women. The oppression on women occurs in two forms i.e. women as a sexual object and slaves. In Greek society, women always become sexual objects based on the behavior shown by men towards women, and men also enslave women. So this study reflects the oppression on women because of the social structure. The findings in this study indicate that the oppression on women during the Trojan War happens due to the social structure of the Greek society that makes women experience oppression.